EVALUATION METHOD OF TERRAIN MONITORING EFFICIENCY BY MEANS OF UNMANNED AERIAL VEHICLES - Yurii G. Danyk; Igor I. Baleckuy (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni, 2018)
In order to increase the efficiency of terrain monitoring (sensing) by means of unmanned aerial vehicles, a method has been proposed for determining the rational trajectories of their flight when performing tasks for surveillance of sectors of the terrain, facilities, etc., and their operational correction. The model of surveillance over the sectors of the terrain has been worked out and considered in order to solve this problem in the context of solving tasks on the state border guarding. The measure of effectiveness concerning the surveillance performance by means of an unmanned aerial vehicle has been proposed when it is located at different points of the airspace. The calculation method of the introduced measure of monitoring efficiency has been proposed.